Fast Synthesis of Hierarchical Co(OH)2 Nanosheet Hollow Spheres with Enhanced Glucose Sensing. Issue 19 (8th June 2016) - Xu, Chufeng; Cao, Yang; Chen, Yong; Huang, Wei; Chen, Delun; Huang, Qingyou; Tu, Jinchun
Abstract : In this report, hierarchical cobalt hydroxide [Co(OH)2 ] hollow spheres composed of nanosheets were synthesized by fast etching of polycrystalline cuprous oxide and were then applied for the nonenzymatic electrochemical detection of glucose. The fabricated hierarchical Co(OH)2 nanosheet hollow spheres were characterized by X‐ray photoelectron spectroscopy, X‐ray diffraction, field‐emission scanning electron microscopy, transmission electron microscopy, and selected area electron diffraction. The electrochemical performance of the hierarchical Co(OH)2 nanosheet hollow spheres modified electrode to detect glucose was investigated by cyclic voltammetry. These sensors exhibited excellent electrocatalytic activity toward glucose, with a response time of less than 5 s. The calibration plot is linear over the wide concentration range of 1 µm to 0.13 mm, with a high sensitivity of 925.21 µA mm –1 cm –2, a correlation coefficient of 0.9942, and a detection limit of 0.93 µm (signal to noise: 3). The results demonstrate that hierarchical Co(OH)2 nanosheet hollow spheres play a vital role in the development of electrochemical sensors for nonenzymatic glucose detection. Abstract : Hierarchical Co(OH)2 hollow spheres composed of nanosheets are synthesized by fast etching of polycrystalline cuprous oxide and are used for the nonenzymatic electrochemical detection of glucose. The shell structure of the hierarchical Co(OH)2 nanosheet hollow spheres is about 50 nm thick, and the sensor shows a high sensitivity of 925.21 µA mm –1 cm –2 and a detection limit of 0.93 µm .